A 'tile' tale: Hierarchical self-assembly of DNA lattices. (March 2016) - Chandrasekaran, Arun Richard; Zhuo, Rebecca
Graphical abstract: Abstract: DNA has been used as a material for the construction of complex nanostructures. Branched DNA molecules can be glued together by sticky end cohesion, providing a route to dictate hierarchical self-assembly of one-, two- and three-dimensional periodic lattices. DNA tiles provide site-specific attachment sites, and can lead to spatially positioned arrays of nanoparticles or macromolecules with nanometer-scale precision. This review discusses the origin and use of various DNA tiles in constructing higher order DNA lattices that can be used as scaffolds for hosting external guests. In addition, the development of DNA origami tiles and arrays is also discussed.